Pemanfaatan Budidaya Tanaman Lada dalam Meningkatkan Pendapatan Masyarakat di Kampung Merancang Ilir Kabupaten Berau - Lindriany, Julita; Rizal, Syamsul; Fritzy, Ikram Nur Zanetty; Hariyani Hairunnisa, Neni; Selfiana, Rani; Salsabila, Rifqah Ainun; Riska, Riska; Hasmah, Siti (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI Sangatta Kab. Kutai Timur., 2025)
This activity was motivated by the significant potential of pepper as a leading commodity capable of boosting community income in Merancang Ilir Village, Berau Regency. The primary objective of this activity was to identify and optimize the benefits of pepper cultivation as a sustainable local economic empowerment strategy. Pepper cultivation was chosen due to its high market value and adaptability to local environmental conditions. The activity implemented a descriptive, qualitative, and participatory approach. Data collection was conducted through field observations, in-depth interviews with farmers and stakeholders, and a structured survey to evaluate income changes and socio-ecological impacts. The research also involved a cost-benefit analysis to measure the economic efficiency of pepper cultivation. The results of the activity showed an average income increase of 35% for the farmer group managing pepper cultivation compared to previous income. Twenty-five farmers joined the farmer group, which actively engaged in collective marketing, technical training, and product diversification, including pepper powder and pepper extract. This activity also strengthened community solidarity and raised awareness of environmentally friendly agricultural practices. In addition to the economic benefits, there were also increased access to education and health services, as well as contributions to local ecosystem preservation through sustainable cultivation techniques. This activity demonstrates that active community involvement in pepper cultivation not only increases income but also strengthens social capacity and environmental sustainability. This underscores the importance of a community-based approach in developing a competitive and inclusive local agricultural sector.